2020
DOI: 10.4269/ajtmh.19-0458
|View full text |Cite
|
Sign up to set email alerts
|

Does Chest Attachment of an Automated Respiratory Rate Monitor Influence the Actual Respiratory Rate in Children Under Five?

Abstract: Pneumonia is one of the leading causes of death in children under 5 years worldwide. In resource-limited settings, WHO recommendations state that pneumonia can be presumptively diagnosed through the presence of cough and/or difficult breathing and a respiratory rate (RR) that is higher than age-specific cutoffs. As a new diagnostic aid the children's automated respiration monitor (ChARM) can automatically measure and classify RR in children under 5 years, but the effect of its chest attachment on the RR has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…According to international guidelines of respiratory infection management, the RR levels are considered to vary in the order of tens of breaths per minute between normal and pathologically fast breathing, 1,10,24 which indicates that NAPPA's accuracy is clearly within the required limits. Substantial differences in individual RR levels are due to many more physiological factors, such as age, 1 altitude, 25 vigilance state, 16,26 position 27 or other acute medical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to international guidelines of respiratory infection management, the RR levels are considered to vary in the order of tens of breaths per minute between normal and pathologically fast breathing, 1,10,24 which indicates that NAPPA's accuracy is clearly within the required limits. Substantial differences in individual RR levels are due to many more physiological factors, such as age, 1 altitude, 25 vigilance state, 16,26 position 27 or other acute medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…22 Development of NAPPA into such diagnostic aid of respiratory infections would require more future studies in comparable settings. 24 Alternatively, NAPPA wearable maybe used as is in academic clinical research for long-term measuring of respiration, activity and position.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, UNICEF launched the acute respiratory infection diagnostic aid (ARIDA) project and determined the target product profile of an automated RR counter [13]. Recently, two automated RR counters, i.e., a photoplethysmography-based (Masimo Rad G) [14][15][16] and accelerometer-based (Philips ChARM) [17][18][19][20] device have been evaluated in a low-resource setting. These studies revealed variable accuracy and some usability issues, such as slow performance and measurement failure [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two automated RR counters, i.e., a photoplethysmography-based (Masimo Rad G) [14][15][16] and accelerometer-based (Philips ChARM) [17][18][19][20] device have been evaluated in a low-resource setting. These studies revealed variable accuracy and some usability issues, such as slow performance and measurement failure [14][15][16][17][18][19][20]. However, for a full evaluation of the value of these two methods to detect fast breathing as a clinical danger sign, field studies should specifically address children with severe febrile illness in a low resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…The low adherence of Nepalese FCHVs to the WHO case management guidelines was primarily a result of a failure to ensure that the child was calm before and during the assessment. A previous study has shown that there is a small risk that ChARM attachment creates fluctuations in the child's RR that lead to misclassification25 ; hence, it is worth further exploring if ChARM device attachment effects children's behaviour and causes them to cry during the assessment. Other contextual factors, such as the low level of literacy, numeracy and training among FCHVs, as well as the remote location of the study where children were not used to strangers and FCHVs saw relatively few children during routine practice: just over five children in 76 days on average.…”
mentioning
confidence: 99%